Biathlon shooting as a model from a biomechanical, kinesiological and psychological perspective -a multidisciplinary approach - Finkenzeller, T.; Sattlecker, G.; Würth, S.; Buchecker, M.; Hödlmoser, K.; Lindinger, S. J.; Amesberger, G. (Sciene and nordic skiing III, 2016)
Biathlon is a very popular Olympic sport in Europe, especially in Germany, Norway, Sweden, Russia and Austria. The media interest and interest of sponsors progressively increased in the last two decades. Going along with the professionalization in broadcasting and in commercialization of the sport, the sport itself got more and more professional in the application of improved sport scientific training methods. Therefore, it is not surprising that the demands of sport scientific expertise expanded in order to optimize biathlon performance. At the Department of Sport Science and Kinesiology of the University of Salzburg, sport scientific diagnostics of biathlon shooting has a long tradition. The first testing was already conducted in 1998. The focus of the first testing was attached towards stance stability and triggering of biathlon shooting. The predominantly biomechanical results and the interpretation of the data were made available to coaches and athletes to optimize the shooting performance. On a research continuum with the opposite ends of basic and applied research as proposed by Atkinson and Nevill (2001), this originally conducted kind of research is placed on the applied research end. Applied research is characterized by examining factors affecting performance in real-sport settings. The aim of applied research is directed on evaluating whether one variable makes a difference to another in the real world. Predominantly, elements of inductive conclusions are drawn, whereas elements of hypothetico-deductive methods are rarely used (Drust, Atkinson, & Reilly, 2007). A theoretically driven research approach is typically difficult to realise in applied research. During and after the testing, athletes and coaches want to receive technological knowledge on improving sports performance, as in our example on improving biathlon shooting performance. Over the years of diagnostics in biathlon shooting, a desire aroused to examine biathlon shooting under a more theoretically driven approach. The knowledge of the first tests were taken up for the development of theoretically grounded research questions. After dealing intensively with biathlon, it turned out that biathlon is a sport offering the possibility to pursue research questions under the perspective of many scientific disciplines. Moreover, biathlon represents a framework being well suited to examine the relationship of exercise and cognition in a real-life setting demonstrating high ecological validity.